298 Leveraging community engagement studios (CE Studios) to develop an interview guide addressing the sexual health needs of justice-involved youth - Chioma Kas-Osoka; Mariah Chambers; Stephania T. Miller; Velma Murry; Jennifer Erves (Journal of Clinical and Translational Science)
Objectives/Goals: 1. Demonstrate the need to apply principles of community-engaged research to various stages of the research process. 2. Outline the process of using CE Studio(s) to redesign an interview guide for service providers of youth involved in the justice system. Methods/Study Population: Service-providers provide a critical lens with which to view the sexual health needs of justice-involved youth. Minimal research describes the unique perspectives of those who work directly with this vulnerable population to address their sexual health needs. The goal of this project is to outline the process of using CE Studio(s) to redesign an interview guide for service providers. The guide is aimed at gathering insight into the knowledge, access, and use of sexual health services for justice-involved youth. Preparation involves the preplanning phase, including the drafting of the interview guide; engagement consists of recruitment and implementation of the CE Studio; and restructuring will outline the application of feedback and finalization of the interview guide. Results/Anticipated Results: During the preparation phase, the researcher was tasked with (1) developing a visual guide to highlight key points of the research study and (2) providing a draft of the tentative interview guide for review prior to the CE Studio session. For the engagement stage, participants were recruited from listservs, community organizations, and word-of-mouth to participate in a session facilitated by a member of the CE Studio team. Lastly, we anticipate that the restructuring phase will not only allow us to use feedback from the CE Studio session to alter the interview guide but provide insight into potential recruitment strategies for the overarching research project. Discussion/Significance of Impact: Leveraging CE Studios to elicit feedback from service providers will provide unique insight into addressing the sexual health needs of justice-involved youth. We expect that the overall CE Studio process and feedback will be integral in eliciting strong qualitative feedback and shaping the implementation of the overall research project.